Comparing time and risk preferences across three post-industrial UK cities. (September 2015) - van der Pol, Marjon; Walsh, David; McCartney, Gerry
Abstract: Time and risk preferences are known to vary considerably across individuals but less is known about the determinants of these individual differences. This paper examines whether preferences vary by geographical location. The motivation for examining geographic heterogeneity is the higher level of mortality experienced in Glasgow over and above that explained by deprivation, sometimes referred to as the 'Glasgow effect'. Data were collected from 3702 individuals across Glasgow, Manchester and Liverpool between July and November 2011. The results show evidence of geographic preference heterogeneity. Contrary to our hypothesis, individuals in Glasgow have a lower rather than higher time preference rate. Individuals in Glasgow are on average more risk seeking compared to Liverpool and more likely to be at the tail end of the distribution (very risk seeking) compared to Manchester. Differences in risk preferences may help explain some of the differences in mortality associated with risky health behaviours such as drug and alcohol use. However, individuals in Glasgow were also more future oriented suggesting that they are less likely to engage in risky healthy behaviours. As the differences in time and risk preferences work in opposite directions in terms of health investments it less likely that these differences can help explain excess mortality in Glasgow. Highlights: Mortality in Glasgow is higher compared to cities with similar levels of deprivation. We investigate whether this may be due to differences in time and risk preferences. A population survey showed that individuals in Glasgow were more risk seeking. Individuals in Glasgow were more rather than less future oriented.